An efficient method of propagating cassava plants using aeroponic culture. Issue 1 (2nd January 2020) - Tokunaga, Hiroki; Anh, Nguyen Hai; Dong, Nguyen Van; Ham, Le Huy; Hanh, Nguyen Thi; Hung, Nguyen; Ishitani, Manabu; Tuan, Le Ngoc; Utsumi, Yoshinori; Vu, Nguyen Anh; Seki, Motoaki
ABSTRACT: Cassava ( Manihot esculenta Crantz) is a root crop grown in tropical and subtropical regions. Cassava production faces an increasing number of new diseases and arthropod pests, especially in Southeast Asia, where its area and trade have expanded. An efficient plant-multiplication system is required to provide disease-free plants to farmers to sustain production. Cassava is generally propagated vegetatively by planting properly lignified stem cuttings in soil. Vegetative multiplication is a simple approach and has the advantage of producing vigorous plants. The generation of new plants from seed, however, is not a common practice. Notably, properly lignified stems, rather than young and non-lignified stems, are required for successful vegetative propagation. On average, it takes approximately 8–12 months to produce lignified stems of sufficient size to establish an efficient and cost-effective propagation system. In the present study, an aeroponic culture system for producing cassava was developed, which is simple, low-cost, and enables the use of young stems (4–6 weeks old) for propagation. Additionally, we have demonstrated that the survival ratio and plant growth are improved in comparison with general propagation in soil. We propose that aeroponic culture can serve as an efficient method for producing disease-free cassava planting material.